2019
DOI: 10.1002/ijc.32591
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom consumption and incident risk of prostate cancer in Japan: A pooled analysis of the Miyagi Cohort Study and the Ohsaki Cohort Study

Abstract: In vivo and in vitro evidence has shown that mushrooms have the potential to prevent prostate cancer. However, the relationship between mushroom consumption and incident prostate cancer in humans has never been investigated. In the present study, a total of 36,499 men, aged 40–79 years, who participated in the Miyagi Cohort Study in 1990 and in the Ohsaki Cohort Study in 1994 were followed for a median of 13.2 years. Data on mushroom consumption (categorized as <1, 1–2 and ≥3 times/week) was collected using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…These include the association of increased mushroom consumption with decreased risks of dementia [ 133 , 134 ], cardiovascular disease, certain cancers (e.g. prostate and breast cancer) [ 135 , 136 ], IBD [ 137 ], metabolic syndrome [ 138 ], PD and other neurological disorders [ 139 ], viral infections [ 140 ] and many other conditions. Some of the studies attributed these perceived health benefits of mushrooms to the ET present [ 129 , [141] , [142] , [143] ].…”
Section: Sources Of Ergothioneinementioning
confidence: 99%
“…These include the association of increased mushroom consumption with decreased risks of dementia [ 133 , 134 ], cardiovascular disease, certain cancers (e.g. prostate and breast cancer) [ 135 , 136 ], IBD [ 137 ], metabolic syndrome [ 138 ], PD and other neurological disorders [ 139 ], viral infections [ 140 ] and many other conditions. Some of the studies attributed these perceived health benefits of mushrooms to the ET present [ 129 , [141] , [142] , [143] ].…”
Section: Sources Of Ergothioneinementioning
confidence: 99%
“…Numerous studies have demonstrated that mushroom consumption can be linked to decreased incidence of chronic diseases of aging such as dementia (19,20) , prostate cancer (21) and risk factors of diabetes (22)(23)(24) . Given the strong associations observed between blood ERGO levels and mushroom consumption (25) , it is possible that many of these beneficial health effects of mushrooms could be attributed to ERGO.…”
Section: The Role Of Ergo In Long-term Human Healthmentioning
confidence: 99%
“…The aforementioned species have been historically used in communities of Taiwan for treating various diseases such as diarrhea, abdominal pain, hypertension, dermatological irritation, and intoxication by food, alcohol, and drugs [ 103 ]. A study tracking 36,499 middle-aged and elderly Japanese men over an average of 13.2 years found a positive relationship between regular mushroom consumption and decreased incidence of prostate cancer [ 104 ]. Table 5 summarizes the classes of compounds and health benefits from some mushroom species cited in this section.…”
Section: Mushrooms As Functional Foods For Preventing Aging-relatementioning
confidence: 99%